COMET: monitoring mitochondrial shock in anesthesiology and intensive care medicine - Yang, Yan; Zhang, Wei; Ma, Zhengliang; Gu, Xiaoping (ANESTHESIOLOGY AND PERIOPERATIVE SCIENCE, 2024)
Mitochondria, as the cellular end-users of oxygen and responsible for approximately 98% of total body oxygen consumption, play a significant role in the development of organ dysfunction during shock. Therefore, integrating information on mitochondrial oxygen homeostasis with macroscopic observations of macrocirculation and microcirculation is crucial for monitoring critically ill patients or those undergoing high-risk surgery. However, current clinical practice still lack reliable surrogate parameters for assessing mitochondrial function. The Cellular Oxygen METabolism (COMET) monitor, utilizing the protoporphyrin IX triplet state lifetime technique (PpIX-TSLT), represents the first clinical device capable of non-invasive, in vivo measurement of mitochondrial oxygen pressure and oxidative phosphorylation. Recent research suggests that implementing this real-time bedside monitoring will provide additional insights into microcirculatory dynamics and enhance patient management. This review will comprehensively detail the rationale, methodologies, evolution, and clinical applications of the technique, aiming at improving the understanding of mitochondrial pathology in daily clinical practice and facilitating the development of targeted therapeutic strategies. Graphical Abstract